Enhancing Fastener Standardization for Disassembly: A Path to Sustainable Laptop Design - Mahmood Khan, Yasin; Fong , Dr. Go Tze; Tai, Vin Cent; Moey, Lip Kean; Ngow , Li Siang; Abd Wahab, Dzuraidah; Yap, Weng Suon (International Journal of Integrated Engineering, 2024)
This project aims to design a laptop for easy of disassembly, thereby reducing disassembly time. The challenges associated with product disassembly include the complexity of replacing worn-out components, managing various types of fasteners, and finding solutions for end-of-life products. This paper focuses on the design for disassembly of laptops by standardizing fasteners to minimize disassembly time. A modified design is proposed to decrease the disassembly time of the laptop compared to the reference design. The laptop components and fasteners are designed using Autodesk Inventor, and the disassembly time is calculated accordingly. The comparison between the new design and the reference design reveals significant improvements in disassembly time for both the laptop screen and keyboard. Specifically, the disassembly time is reduced by a factor of 4 for the laptop screen and 4.5 for the keyboard. Furthermore, the number of required disassembly tools is reduced from three different screwdrivers to just one. The primary objective of the new laptop design is to ensure easy disassembly and reassembly. By making product components easily accessible for repair, replacement, recycling, and reuse, this design not only saves time and resources for manufacturing and recycling companies but also reduces labor costs. It enhances customer satisfaction and minimizes the time and effort required for quick disassembly during product repair and refurbishment. In conclusion, Design for Disassembly is an effective approach for creating sustainable products that can be easily disassembled, facilitating simpler maintenance, repair, recovery, and reuse of components and materials.